2016
DOI: 10.1111/cge.12888
|View full text |Cite
|
Sign up to set email alerts
|

A novel gain‐of‐function mutation in ORAI1 causes late‐onset tubular aggregate myopathy and congenital miosis

Abstract: We present three members of an Italian family affected by tubular aggregate myopathy (TAM) and congenital miosis harboring a novel missense mutation in ORAI1. All patients had a mild, late onset TAM revealed by asymptomatic creatine kinase (CK) elevation and congenital miosis consistent with a Stormorken-like Syndrome, in the absence of thrombocytopathy. Muscle biopsies showed classical histological findings but ultrastructural analysis revealed atypical tubular aggregates (TAs). The whole body muscle magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
2
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 14 publications
3
57
2
7
Order By: Relevance
“…Active CRAC Channels. Several recent studies have described GOF missense Orai1 mutations in TMs 2-4, with some linked to tu-bular aggregate myopathy with additional symptoms including thrombocytopenia and miosis (12)(13)(14)(15). The identification of GOF mutations in the non-pore-lining segments suggests that these domains of Orai1 may play a greater role in channel activation than previously appreciated.…”
Section: Scanning Mutagenesis Of Orai1 Tms Reveals Numerous Constitutmentioning
confidence: 99%
See 3 more Smart Citations
“…Active CRAC Channels. Several recent studies have described GOF missense Orai1 mutations in TMs 2-4, with some linked to tu-bular aggregate myopathy with additional symptoms including thrombocytopenia and miosis (12)(13)(14)(15). The identification of GOF mutations in the non-pore-lining segments suggests that these domains of Orai1 may play a greater role in channel activation than previously appreciated.…”
Section: Scanning Mutagenesis Of Orai1 Tms Reveals Numerous Constitutmentioning
confidence: 99%
“…2 and SI Appendix, Table S1). These included two loci that have been linked to tubular aggregate myopathy with congenital miosis-S97C on the non-pore-lining face of TM1 (13) and P245C in TM4 (12)-as well as H134C in TM2, F187C in TM3, and A235C in TM4 (Figs. 1 and 2 and SI Appendix, Table S1).…”
Section: Scanning Mutagenesis Of Orai1 Tms Reveals Numerous Constitutmentioning
confidence: 99%
See 2 more Smart Citations
“…Human studies have shown that loss of CRAC channel function leads to a devastating immunodeficiency along with additional symptoms of autoimmunity, ectodermal dysplasia, and muscle defects, highlighting the vital importance of CRAC channels for human health [79]. Conversely, constitutive channel activation from gain-of-function mutations in CRAC channel proteins are linked to pathologies such as tubular aggregate myopathy and thrombocytopenia [1012]. In several instances, the molecular mechanisms of how these loss- and gain-of-function mutations disrupt CRAC channels remains unclear, underscoring the need for a better understanding of the operational mechanisms of CRAC channels including their gating mechanism.…”
Section: Introductionmentioning
confidence: 99%